Studies on cultural, morphological, pathogenic and molecular variability of Alternaria brassicae, the causal agent of blight disease of rapeseed-mustard (Journal of Oilseed Brassica, 2026)
In India, rapeseed-mustard is one of the most edible oilseed crops after groundnut and contributes around 26.1 per cent of the total oilseed production. Among Brassica oil seed crops, Indian mustard [Brassica juncea (L.) Czern & Coss.] is commonly cultivated in most of the Indian states. Alternaria blight disease caused by A. brassicae has been reported from all the continents of the world causing up to 47 per cent yield losses with no proven source of resistance. The present investigation was carried out to study the cultural, morphological, pathogenic and molecular variability among A. brassiace isolates collected from different Brassica spp. (Pantnagar) and from different geographical locations of India (Karnal, Punjab, Bihar, Jammu and Kangra) to exploit them in breeding programme during screening for resistance sources and selection of host differentials. In the present studies A. brassicae isolates (20 nos.) showed the existence of genetic diversity. Significant variation in cultural, morphological, pathogenic and molecular variability was observed in A. brassiace isolates irrespective to geographical locations and Brassica spp. Maximum radial growth (82.0 mm) was in AB-B. juncea Pantnagar isolate, while minimum in AB- B. caulorapa (49.7 mm) on PDA. Variations were also observed in colony colour, appearance, margin and zonation number. Substantial variations were found in spore morphology in respect to conidial length, width and number of septa. Average conidial length and width were varied from 29.0-6.6 x 185.3-28.2μm. Maximum spore length and width was in AB-B. carinata isolate (185.3 x 25.6 μm), while minimum in AB-B. caulorapa (29.0 x 6.6μm). Number of horizontal and vertical septa ranged between 3.50-14.75 and 0.75-5.0 respectively. All the isolates were pathogenic to Brassica spp. AB-B. juncea Pantnagar isolate was most virulent, while AB-S. alba least virulent. RAPD (18 no.) and ISSR (4 no.) primers generated a total of 310 reproducible and scorable polymorphic bands ranged from 100 to 1350 bp which displayed genetic polymorphisms among the A. brassicae isolates. On the basis of cultural, morphological, pathogenic and molecular variability, the A. brassiace isolates has been categorized into 5 major groups. Group I: AB-R. sativus, AB-B. pekinensis, AB-B. oleracea, AB-B. botrytis and AB-B. caulorapa; Group II: ABB. juncea Pantnagar, AB-Yellow sarson, AB-Toria, AB-B. nigra, AB-R. oleifera, AB-B. juncea Karnal, ABB. juncea Punjab and AB-B. juncea Bihar; Group III: AB-B. napus, AB-B. carinata, AB-E. sativa , AB-S. alba; Group IV: AB-B. juncea Kangara and AB-B. juncea Jammu; Group V: AB-B. rugosa. The different Brassica spp. (08 nos.) used in the present investigation to differentiate different A. brassicae isolates (09 nos.) as host differentials has been categorized into 4 major groups on the basis of differential phenotypic disease reactions. Group I: Varuna, PT-303, PYS-6 and B. nigra; Group II: PBN-9501 and Kiran; Group III: E. sativa; Group IV: S. alba. Among different methods of culture preservation of A. brassicae isolates, 10 per cent glycerol at -20ºC was best in terms of sporulation (66.7%) followed by PDA at 4ºC (65.7%) and could be used for the preservation of A. brassicae isolates at least two years.